Measuring the Effects of Trade Liberalization in Kosovo - Mario Holzner; Florin Peci (The Vienna Institute for International Economic Studies (wiiw), 2012)
Similar to other countries in the European periphery, Kosovo lacks competitiveness, has adopted the euro as its national currency and started an integration process with the EU. The next milestone in this process is the signing of an FTA with the EU. We simulate full trade liberalization vis-à-vis the EU, using the Global Simulation Model. Our results suggest a slight output loss in almost all industries in Kosovo due to a drop in prices. Moreover the government budget is expected to lose about 5% of its revenues due to the tariff cut. A shift towards more direct taxation and measures aimed at improving the investment climate in Kosovo are recommended.
Keywords: F15; F17; P33; 330; trade policy simulation; Kosovo; EU integration